Study on slope stability during tunnel construction in water rich soft soil area. Issue 1 (May 2021) - Xiong, Qihuan; Yuan, Qing; Shen, Jiuzhou; Yang, Lin; Cheng, Shihao; Zhang, Ziping
Abstract: Based on the relationship between soil strength index and water content, the stability of tunnel portal slope during tunnel excavation in water rich soft soil area is analyzed according to the change of soil water content under different working conditions during tunnel construction. The results show that the strength index of soil decreases in inverse proportion with the increase of saturation. Reasonable excavation speed or effective dewatering measures are conducive to the self stability of the open cut slope. When the duration of heavy rainfall does not exceed 2 h, the slope is in a stable state; when the duration reaches 10 h, the slope enters the limit equilibrium state; when the duration reaches 18 h, the slope enters the failure state.